Targeting glioblastoma via intranasal administration of Ff bacteriophages - Dor-On, Eyal; Solomon, Beka (Frontiers in Microbiology, 2015)
Bacteriophages (phages) are ubiquitous viruses that control the growth and diversity of bacteria. Although they have no tropism to mammalian cells, accumulated evidence suggests that phages are not neutral to the mammalian macro-host and can promote immunomodulatory and anti-tumorigenic activities. Here we demonstrate that Ff phages that do not display any proteins or peptides could inhibit the growth of subcutaneous glioblastoma tumors in mice and that this activity is mediated in part by lipopolysaccharide molecules attached to their virion. Using the intranasal route, a non-invasive approach to deliver therapeutics directly to the CNS, we further show that phages rapidly accumulate in the brains of mice and could attenuate progression of orthotopic glioblastoma. Taken together, this study provides new insight into phages non-bacterial activities and demonstrates the feasibility of delivering Ff phages intranasally to treat brain malignancies.